Indonesian in the Vortex of Policy Change Final Project: Challenges and Strategies for Maintaining Academic Competence - Mulyaningsih, Indrya; Munsi, Mia Fatimatul; Rochmansyah, Bagaskara Nur (Universitas PGRI Sumatera Barat, 2025)
This study aims to: 1) analyze the implications of the policy on students' competence in using scientific Indonesian, and 2) evaluate the impact of eliminating the thesis as a medium for developing academic writing. Data were collected through interviews, questionnaires, and document analysis at 9 universities ranked in the top 25 according to Time Higher Education (THE) for the June 2023 period. This study reveals that the policy of eliminating the obligation to write a thesis in Permendikbudristek No. 53/2023 has the potential to reduce students' competence in mastering scientific Indonesian. Indonesian remains important as the main medium in developing critical thinking skills, scientific argumentation, and academic communication in various forms of alternative final assignments, such as projects, prototypes, or other innovative works. Good and correct mastery of Indonesian remains an important pillar in ensuring the quality of learning outcomes and student contributions in the academic and professional world. The implication is that it is necessary for the Directorate General of Higher Education to prepare technical implementation guidelines that regulate: 1) minimum language content standards for all types of final assignments, 2) validation mechanisms for Indonesian language competency, for example with the Indonesian Language Proficiency Test (UKBI), and 3) allocation of special credits for academic writing training so that mastery of Indonesian remains the foundation of academic competency for university graduates.